Peran Literasi Keuangan dan Literasi Digital dalam Meningkatkan Kinerja UKM - Kurnia, Meydica Indah; Indriani, Rini (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study analyzes the role of financial literacy and digital literacy in improving the performance of medium-sized enterprises in Bengkulu City. The main problem studied is the low growth rate of MSMEs due to limited understanding of finance and digital technology. The study used a quantitative approach with purposive random sampling technique on 273 respondents from a population of 1,102 medium enterprises. Data were collected through a questionnaire measured by a Likert scale and analyzed using multiple linear regression. Prior to analysis, data quality test, classical assumption test, and model feasibility test were conducted. The results showed that financial literacy has a significant positive effect on the performance of medium-sized enterprises with a significance value of 0.001<0.05, proving that an understanding of budgeting, savings, loans, and investments contributes to performance optimization. Digital literacy also has a significant positive effect on business performance with a significance value of 0.001<0.05, indicating that the ability to utilize digital technology increases efficiency and competitiveness. The coefficient of determination of 73,7% indicates that both variables play an important role in explaining the performance of medium-sized enterprises. The study concluded that strengthening financial and digital literacy is an effective strategy to improve the performance of medium-sized enterprises in facing the competitive digital economy era.